Oral vancomycin treatment does not alter markers of postprandial inflammation in lean and obese subjects. Issue 16 (18th August 2019) - Bakker, Guido J.; Schnitzler, Johan G.; Bekkering, Siroon; de Clercq, Nicolien C.; Koopen, Annefleur M.; Hartstra, Annick V.; Meessen, Emma C. E.; Scheithauer, Torsten P.; Winkelmeijer, Maaike; Dallinga‐Thie, Geesje M.; Cani, Patrice D.; Kemper, Elles Marleen; et al.
Abstract: Intake of a high‐fat meal induces a systemic inflammatory response in the postprandial which is augmented in obese subjects. However, the underlying mechanisms of this response have not been fully elucidated. We aimed to assess the effect of gut microbiota modulation on postprandial inflammatory response in lean and obese subjects. Ten lean and ten obese subjects with metabolic syndrome received oral vancomycin 500 mg four times per day for 7 days. Oral high‐fat meal tests (50 g fat/m 2 body surface area) were performed before and after vancomycin intervention. Gut microbiota composition, leukocyte counts, plasma lipopolysaccharides (LPS), LPS‐binding protein (LBP), IL‐6 and MCP‐1 concentrations and monocyte CCR2 and cytokine expression were determined before and after the high‐fat meal. Oral vancomycin treatment resulted in profound changes in gut microbiota composition and significantly decreased bacterial diversity in both groups (phylogenetic diversity pre‐ versus post‐intervention: lean, 56.9 ± 7.8 vs. 21.4 ± 6.6, P  < 0.001; obese, 53.9 ± 7.8 vs. 21.0 ± 5.9, P  < 0.001). After intervention, fasting plasma LPS significantly increased (lean, median [IQR] 0.81 [0.63–1.45] EU/mL vs. 2.23 [1.33–3.83] EU/mL, P  = 0.017; obese, median [IQR] 0.76 [0.45–1.03] EU/mL vs. 1.44 [1.11–4.24], P  = 0.014). However, postprandial increases in leukocytes and plasma LPS were unaffected by vancomycin in both groups. Moreover, we found no changes in plasma LBP, IL‐6 and MCP‐1 or in monocyte CCR2 expression. Despite major vancomycin‐induced disruption of the gut microbiota and increased fasting plasma LPS, the postprandial inflammatory phenotype in lean and obese subjects was unaffected in this study. Abstract : Translocation of intestinal bacteria into the blood is implicated in the systemic inflammatory response that occurs after a high fat meal. We showed that after gut microbiota manipulation with vancomycin, the postprandial inflammatory phenotype in lean and obese subjects is unaffected, despite major vancomycin‐induced disruption of the gut microbiota and increased fasting plasma LPS. This suggests that bacterial translocation may not play a large role in postprandial inflammation.